“Innovative Approaches to Sustainability in Human Resource Management: A Review of Strategies, Challenges, and Future Directions” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Sustainable Human Resource Management (S-HRM) has emerged as a critical domain linking organizational strategy, environmental stewardship, and employee-centred sustainability practices. However, existing scholarship remains conceptually fragmented, with limited systematic mapping of its intellectual structure. Addressing this gap, the present study employs a bibliometric and text-mining approach to analyse 784 peerreviewed publications using Latent Dirichlet Allocation (LDA) topic modelling and Multidimensional Scaling (MDS).The analysis identifies five dominant thematic clusters: Green HR & Environmental Sustainability, Strategic HR Frameworks, Employee Behaviour & Knowledge Sharing, Innovation & Technological Transformation, and Leadership & Engagement. Topic coherence testing and interpretability validation supported the selection of the five-topic solution. The MDS visualization reveals significant convergence between leadership-driven engagement and green HR practices, suggesting an increasing behavioural orientation in sustainability research. In contrast, technology-driven sustainability remains comparatively isolated, indicating a structural gap between digital innovation and human-centred sustainability discourse.Building on these findings, the study proposes an integrated multi-layered conceptual framework positioning strategic alignment as the foundational driver, leadership and engagement as behavioural catalysts, and environmental and innovation outcomes as strategic extensions. By shifting from narrative synthesis to datadriven intellectual mapping, this research advances theoretical integration within S-HRM scholarship.Practically, the findings underscore the importance of aligning leadership development, employee engagement, and digital transformation initiatives with sustainability objectives, particularly in the context of the United Nations Sustainable Development Goals (SDGs). The study provides a systematic roadmap for future interdisciplinary research bridging behavioural, strategic, and technological perspectives in sustainable HRM.